Distribution of nanoparticles throughout the cerebral cortex of rodents and non-human primates: Implications for gene and drug therapy - Salegio, Ernesto A.; Streeter, Hillary; Dube, Nikhil; Hadaczek, Piotr; Samaranch, Lluis; Kells, Adrian; San Sebastián, Waldy; Zhai, Yuying; Bringas, John; Xu, Ting; Forsayeth, John; Bankiewicz, Krystof S. (Frontiers in Neuroanatomy, 2014)
When nanoparticles/proteins are infused into the brain, they are often transported to distal sites in a manner that is dependent both on the characteristics of the infusate and the region targeted. We have previously shown that adeno-associated virus (AAV) is disseminated within the brain by perivascular flow and also by axonal transport. Perivascular distribution usually does not depend strongly on the nature of the infusate. Many proteins, neutral liposomes and AAV particles distribute equally well by this route when infused under pressure into various parenchymal locations. In contrast, axonal transport requires receptor-mediated uptake of AAV by neurons and engagement with specific transport mechanisms previously demonstrated for other neurotropic viruses. Cerebrospinal fluid (CSF) represents yet another way in which brain anatomy may be exploited to distribute nanoparticles broadly in the central nervous system. In this study, we assessed the distribution and perivascular transport of nanoparticles of different sizes delivered into the parenchyma of rodents and CSF in non-human primates.